Geometric flows and Strominger systems - Phong, Duong H.; Picard, Sebastien; Zhang, Xiangwen (Mathematische Zeitschrift, 2018)
A geometric flow on (2, 2)-forms is introduced which preserves the balanced condition of metrics, and whose stationary points satisfy the anomaly equation in Strominger systems. The existence of solutions for a short time is established, using Hamilton’s version of the Nash–Moser implicit function theorem.